High take off left main coronary artery accompanied by multicryptic left ventricle myocardium detected by cardiac computerized tomography in a young male: case report - Özge Ozden Tok; Ignatios Ikonomidis; Konstantinos Papadopoulos; Ömer Göktekin; Gülsüm Bingöl; Giovanni Di Salvo (BMC Cardiovascular Disorders, 2021)
Abstract Background Myocardial crypts are discrete, narrow, blood filled invaginations within the left ventricular myocardium and high-take-off coronary artery are rare manifestations where coronary arteries originate above the sinotubuler junction. Case presentation A 41-year-old man with multiple coronary artery disease risk factors admitted to our outpatient department with progressive dyspnea and atypical chest pain. Physical examination revealed no pathological findings. His blood examination revealed only mild to moderately high IgE and LDL levels. Transthoracic echocardiography (TTE) was normal. His treadmill test was normal, yet in the 3rd stage of the test he had an atypically located chest pain which was relieved in the resting period. As he had multiple cardiovascular risk factors, we performed a coronary CT angiography to exclude coronary artery disease. Coronary CT angiography(CCTA) demonstrated multiple myocardial crypts, a muscular VSD like defect which were not detectable with TTE and a high take off left main coronary artery (LMCA). After CCTA, we repeated the TTE to investigate the crypts and VSD-like defect which were clear on CCTA, yet a precise TTE hardly showed crypts and didn’t confirm a shunt between the left and right ventricle. We defined the defect as ‘spontaneously closed muscular VSD’. None of these pathologies were clinically relevant with the patient’s symptoms, thus pneumonology started a montelukast therapy for 1 year and we decided to follow up the patient, as multiple crypts may indicate an early phase hypertrophic cardiomyopathy. Conclusions Considering that a high take-off LMCA is a congenital anomaly, encountering multiple crypts which are also congenital pathologies, is plausible, as congenital anomalies may accompany eachother. Echocardiography is a very useful, practical imaging tool but regrettably may be suboptimal due to various patient and method related reasons. Target combination of different cardiovascular imaging tools like echocardiography, cardiac CT(CCT), may be utilized in order to ensure a comprehensive diagnosis particularly.